2004
DOI: 10.1007/s11664-004-0049-2
|View full text |Cite
|
Sign up to set email alerts
|

Annealing effects of a high-quality ZnTe substrate

Abstract: The sharp photoluminescence (PL) and optical-reflection spectra in the bandedge region of the high-quality nondoped ZnTe substrate (100) were observed at 4.2 K. Free exciton, associated with lower and upper polaritons (EX L and EX U ) at 2.382 eV and 2.381 eV, respectively, were clearly observed. This meant that this substrate was high quality. The intensity of a bound exciton peak (2.375 eV), which is caused by a Zn vacancy, of a neutral acceptor decreased with an increase of the Zn vapor pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
(14 reference statements)
1
11
0
Order By: Relevance
“…Previous secondary ion mass spectroscopy analysis on nominally undoped ZnTe epitaxial layers showed that Na acts as a dominant impurity 14. It is worth noting that both the Y lines usually at 2.188 and 2.147 eV which are known to arise due to extended structural defects 15, and donor–acceptor pair (DAP) emission at 2.33 eV which is because of the recombination from between the Zn vacancy ( V Zn ) acceptor and Te vacancy ( V Te ) donor or between Zn interstitial (Zn i ) donor and Te interstitial (Te i ) acceptor 16, are not observed in the structures 17. Also, oxygen‐bound‐exciton (OBE) emission band around 650 nm whose zero‐phonon line locates at around 1.986 eV, reported by Ekawa and Taguchi 18 and Zhang et al 19, does not appear in all the epilayers.…”
Section: Resultsmentioning
confidence: 99%
“…Previous secondary ion mass spectroscopy analysis on nominally undoped ZnTe epitaxial layers showed that Na acts as a dominant impurity 14. It is worth noting that both the Y lines usually at 2.188 and 2.147 eV which are known to arise due to extended structural defects 15, and donor–acceptor pair (DAP) emission at 2.33 eV which is because of the recombination from between the Zn vacancy ( V Zn ) acceptor and Te vacancy ( V Te ) donor or between Zn interstitial (Zn i ) donor and Te interstitial (Te i ) acceptor 16, are not observed in the structures 17. Also, oxygen‐bound‐exciton (OBE) emission band around 650 nm whose zero‐phonon line locates at around 1.986 eV, reported by Ekawa and Taguchi 18 and Zhang et al 19, does not appear in all the epilayers.…”
Section: Resultsmentioning
confidence: 99%
“…A modest energetical displacement of lines in spectra from epitaxial films comparing to those from the polycrystalline layers films deposited on glass may be caused by presence of sufficient macrodeformations in the layers CdTe/BaF2. PL spectra from CdTe layers have lines originated from optical transfers with participation of free and bound excitons, transfers valence band -acceptor ( -А), donor-acceptor transfers (DAP), the radiation caused by presence of dislocations or DP (donor pairs, DP) (Y -stripes); the spectra also have a set of lines corresponding to optical transitions where phonons take place (LO -phonon replica) [87][88][89][90][91][92][93][94][95][96][97][98][99]. Activation energies relative to the valence band (while the most samples were of p-type conductivity) were calculated using expression (26) (in analogy with description above).…”
Section: Determination Of Ls Parameters Of Polycrystalline Chalcogenimentioning
confidence: 99%
“…Table 7. Analysis and interpretation of the PL peaks are carried out according to reference data [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89]. We calculated activation energies of corresponding processes using the expression (26).…”
Section: сDte Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…ZnTe single crystal is a promising material for applications in green light emitting diodes (LEDs), laser diodes (LDs), solar cells, microwave devices, and terahertz devices [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%